BLENDED WORSHIP: MAENA DANCE TRADITION - Sudirman Lase; Testi B. Zebua; Irwansyah; Apriliana Lase (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The Nias community is unique and has a different cultural culture from other regions in North Sumatra. One of the unique things done in the traditional celebration of marriage/wedding by doing activities in the form of dances is called Maena. Maena is a traditional Nias dance with a simple movement pattern that is easy to learn. Maena is usually performed by a group of Sanötöi Maena (poet/singer) and ono maena (dancer). The research gap of this study is to focus on applying the value of local wisdom and religious values to the BNKP worship system on Nias, which has never been studied by previous research. The research was conducted in Gunung Sitoli, Nias Island, North Sumatra. The theoretical framework in this research is ethnography and data collection techniques use observation, interviews, video documentation and content analysis. Additional data information was obtained through observations and interviews with the Nias community. The traditional dance in the offering procession during worship at BNKP is a combination that creates a combination of local wisdom by involving culture by providing elements of a blend of church music so as to instill familial religious values at BNKP. Maena is the choice in the process of adopting local wisdom involved in worship at BNKP. The people of Nias feel inner satisfaction when they participate in making foot and hand movements and singing maena songs, this is a form of joy.